Effect of cinnamaldehyde on interfacial rheological properties of proteins adsorbed at O/W interfaces. (December 2019) - Felix, Manuel; Yang, Jack; Guerrero, Antonio; Sagis, Leonard M.C.
Abstract: The dynamics of heterogeneous food products such as emulsions can be affected significantly by the interfacial properties of their interfaces. Proteins are widely used to increase the stability of these food products. This work compares the interfacial properties of a model protein (whey protein isolate, WPI) and silkworm pupae (SLW) adsorbed at the O/W interface. A natural aldehyde (cinnamaldehyde, CNM) was used for both protein systems in order to promote protein-protein interactions. Interfacial properties were characterised during protein adsorption and after reaching a quasi-equilibrium state by means of oscillatory and step dilatational, and oscillatory interfacial shear measurements. The results obtained from dilatational and interfacial shear tests showed that the use of CNM resulted in the development of stronger interfaces, with higher values for the dilatational and surface shear storage moduli, and a lower loss tangent. Step-dilatation tests indicated that the addition of CNM also resulted in more homogeneous interfaces. Our results show that CNM addition can enhance the surface properties of SLW, to a level which is close to the properties of un-modified WPI stabilized interfaces. Graphical abstract: Image 1055709 Highlights: The use of CNM resulted in the development of stronger interfaces. The homogeneity of the interface increased after CNM addition. CNM addition enhances the surface properties (dilatational and shear) of SLW film. The interfacial properties of SLW-CNM system are close to un-modified WPI.